Cellular basis of learning and memory in the carotid body - Gold, Olivia M. S.; Bardsley, Emma N.; Ponnampalam, Anna P.; Pauza, Audrys G.; Paton, Julian F. R. (Frontiers in Synaptic Neuroscience, 2022)
The carotid body is the primary sensor of blood gases in the body, and critical for respiration and cardiovascular control. Yet considerable evidence now implicates the carotid body in a multitude of sensory roles, including pH, temperature, and acidosis as well as hormonal and glucose, and possibly immune regulation. How does the carotid body detect and initiate appropriate physiological responses for these diverse stimuli? The answer to this may lie in the structure of the carotid body itself. We suggest that at an organ-level, compartmentalized discrete regions of clustered glomus cells may be defined by their neurotransmitter expression and receptor profiles, and the connectivity of these regions to defined reflex arcs may play a key role in initiating distinct physiological responses, similar in many ways to a switchboard that connects specific inputs to selective outputs. Similarly, within the central nervous system, specific physiological outcomes are coordinated, through signaling via distinct neuronal connectivity. We propose that highly organized cellular connectivity is also critical for mediating coordinated outputs from the carotid body to a given stimulus. Moreover, it appears that the rudimentary components for synaptic plasticity, and learning and memory are conserved in the carotid body including the presence of glutamate and GABAergic systems, where some evidence suggests that pathophysiology of common diseases of the carotid body may be linked to deviations in these processes. Several decades of research have contributed to our understanding of the central nervous system in health and disease, and we discuss that understanding the key processes involved in neuronal dysfunction and synaptic activity may be applicable to the carotid body, offering new insights and avenues for therapeutic innovation.